Intrahepatic and Extrahepatic Cholestatic Jaundice Caused by Adenocarcinoma Pancreas with Hepatitis B Infection: A Case Report - Tris Mardi; Arnelis (HM Publisher, 2022)
Background: Cholestasis is defined as the stagnation of biliary duct secretion. Intrahepatic jaundice cholestasis is caused by inflammation that happens intrahepatic from an infection such as hepatitis. Meanwhile, extrahepatic cholestasis is caused by obstruction of the biliary duct outside the liver. Stagnation of the bile flow due to these couple of conditions occurring concurrently has been rarely reported. Biliary duct stagnation that occurs with an infection of hepatocytes will cause more serious and progressive effects. Case presentation: A 73 years old woman with extrahepatic and intrahepatic cholestasis caused by pancreatic adenocarcinoma along with chronic hepatitis B. The diagnosis is made based on clinical findings, lab findings, and radiology findings. Quick action is mandatory to prevent complications caused by hyperbilirubinemia and slows the progression of hepatitis B-induced liver fibrosis. A Whipple procedure was performed on this patient to treat the biliary duct obstruction. The patient's condition improved after surgery. The patient is then planned to be given adjuvant chemotherapy, preceded by the administration of antivirals for hepatitis. Conclusion: Cholestasis jaundice causes hyperbilirubinemia that presents with clinical complaints such as jaundice, itchy and could cause several complications due to damage to the liver tissue whose clinical manifestations are related to impaired liver function caused by hyperbilirubinemia in the form of hypoalbumin, hypercoagulation, and in advanced stages can end up with liver cirrhosis. The principle management for cholestatic jaundice is bile duct decompression which is expected to rule out the etiology of the blockage. Tenofovir was given before chemotherapy in these patients to prevent hepatitis flare due to hepatitis B.